Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, dan Ukuran Perusahaan Terhadap Kinerja Perusahaan - Putri Ramalia Yusmir; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2024)
This research examines the influence of managerial ownership, institutional ownership and company size on company performance in mining companies listed on the Bursa Efek Indonesia for the 2019-2022 period. Company performance is calculated using the Tobins' Q measurement. The sampling method for this research uses purposive sampling and 28 mining companies were obtained as samples. The type of data used is secondary data using panel data regression. The research results state that the managerial ownership variable has a negative and significant effect on company performance. The variables institutional ownership and company size have no effect on company performance.